THE EFFECT OF LEADERSHIP AND THE IMPLEMENTATION OF THE FINGERPRINT ABSENCE MODEL ON WORK PRODUCTIVITY WITH WORK DISCIPLINE AS A MODERATING VARIABLE OF AUTOMOTIVE COMPANIES IN INDONESIA - Netty Laura S (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
This study aims to analyze the influence of Leadership and Application of Fingerprint Attendance Model to Work Productivity With Work Discipline as Moderating Variable. In this research, sampling method used is accidental sampling method (non-probability sampling). In this study using three variables, independent variables are Leadership (X1) and Attendance Model Fingerprint (X2) with dependent variable is Productivity (Y) and moderating variable is Discipline (Z). Population in this research is employees at PT. ASTRA Daihatsu Motor, and samples are 85 respondents. The result of the research shows that Leadership variable is not able to moderate to Work Productivity, Fingerprint Attendance Model variable has a significant effect on Work Productivity, Work Discipline variable also has a significant effect on Work Productivity, Leadership and Work Discipline is not able to moderate to Work Productivity, Fingerprint and Discipline Attendance Model Work is also not able to moderate against Work Productivity.